FAKTOR-FAKTOR PENENTU KEBERHASILAN USAHA PADA PEMEGANG USAHA WARALABA (Studi Kasus Pada UsahaWaralaba Makanan dan Minuman Lokal Di Kota Semarang - Pamungkas, Rizki; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2014)
Business franchise (franchise) is now growing in Indonesia. This is because in Indonesia with a population of over 200 million people who have the biggest market opportunity. One type of franchise that is being developed at this time is the category of food and beverage franchise locally. This study aims to determine the influeace of to determine the influence of business characteristic, business location, and management ability about success business franchising in Semarang. And to analysis the dominant factor in a successful business franchising in Semarang.The populations used in this study iis the holder of franchise business in Semarang. Samples taken are as many as 82 respondents, by using Non-Probability Sampling method and Accidential Sampling approaches, that is the sample determination method based on coincidence, which are the holders of franchise business in Semarang. According to the stastictical data analysis, the outcome is that the indicators used in this study are valid and the variables are reliable. The classical assumption test, that is multicolinnearity regression model, indicate that there is no hsteroscedasticity, and the distribution is normal.